Pengaruh Brand Image Dan Harga Terhadap Keputusan Pembelian Laptop Asus (Studi Kasus Pada Mahasiswa FEB UISU Prodi Manajemen Stambuk 2020) - Nabila, Wavira Eisya; Helmi, Tengku Ahmad; Julkarnain, Julkarnain (JRMB (Jurnal Riset Manajemen & Bisnis), 2022)
The formulationof the probleminthisstudyiswhetherthereis aneffectof Brand ImageandPriceonPurchasing Decisions forAsusLaptops(CaseStudyofFEB UISUManagement StudyProgramStudentsStambuk2020).Thisstudyaimsto determine theeffectofBrandImage andPriceonAsus LaptopsPurchasing Decisions(CaseStudyofFEBUISUManagement StudyProgramStudents Stambuk2020).Thepopulation ofthisstudywere160FEBUISUManagement StudyProgramstudentsusingtheSlovinsamplingformulaobtaineda samplesize of62samples andallocatedtoeachstratum usingthesimplerandomsampling formula.Datacollectiontechniquesinthisstudyusingquestionnaires and literature studies.Thedataanalysis technique usedinthisresearchismultiple linearregression analysis.Thedatacalculation processusestheSPSS20 programme. TheresultsofthisstudyindicatethatBrandImagehasasignificant effectonPurchasingDecisionsforAsusLaptopsforFEBUISUManagementStudy ProgramStudentsStambuk2020.Pricehasasignificant effectonpurchasing decisions forAsuslaptops forFEBUISUstudentsinthe 2020The formulationof the probleminthisstudyiswhetherthereis aneffectof Brand ImageandPriceonPurchasing Decisions forAsusLaptops(CaseStudyofFEB UISUManagement StudyProgramStudentsStambuk2020).Thisstudyaimsto determine theeffectofBrandImage andPriceonAsus LaptopsPurchasing Decisions(CaseStudyofFEBUISUManagement StudyProgramStudents Stambuk2020).Thepopulation ofthisstudywere160FEBUISUManagement StudyProgramstudentsusingtheSlovinsamplingformulaobtaineda samplesize of62samples andallocatedtoeachstratum usingthesimplerandomsampling formula.Datacollectiontechniquesinthisstudyusingquestionnaires and literature studies.Thedataanalysis technique usedinthisresearchismultiple linearregression analysis.Thedatacalculation processusestheSPSS20 programme. TheresultsofthisstudyindicatethatBrandImagehasasignificant effectonPurchasingDecisionsforAsusLaptopsforFEBUISUManagementStudy ProgramStudentsStambuk2020.Pricehasasignificant effectonpurchasing decisions forAsuslaptops forFEBUISUstudentsinthe2020Stambuk Management StudyProgram.BrandImageandPricesimultaneouslyhavea significant effectonPurchasing DecisionsforAsusLaptopsforFEBUISU StudentsinManagementStudyProgramStambuk2020.